Speciation of the polycyclic aromatic hydrocarbons (PAHs) in scallions (Alium chinese; order; asterales; family; Asteraceae) cultivated on the shoulder of intracity highways in Lagos, Nigeria - Ogwu, C.; Anani, O. A.; Imobighe, M.; Nwadiolu, R.; Agbe, E. (International Journal of Agricultural Technology, 2025)
The comparative mean results obtained in this study showed the following: pyrene 2.94±0.11 µg/g, chrysene 3.01±0.23 µg/g, BaP; 2.94±0.13 µg/g, BaA; 3.01±0.12 µg/g and BbF; 3.04±0.13 µg/g. The results of the health evaluation showed that Beneze (a) pyrene had the highest value (14.71 µg/kg), followed by Benze (b) fluoranthene and Benzo (a) anthracene (1.52 and 1.51) of the toxicity equivalent factors. Meanwhile, the sum across the station was significantly higher than the standard limits. The CDI (chronic daily intake) results obtained for each PAH congener were considerably high and fluctuated across the station. However, the results for the ILCR (incremental life cancer risk) were higher than the threshold set for this study. The study concluded that the content of PAH investigation in the scallions was higher than the set threshold. It is recommended that the cultivation of scallions on the highway shoulders be discontinued. Farmer's advocacy and education were imperative to enlighten the farmers on the adverse effects of farming along the road shoulders, and the implications of producing such vegetables for human consumption.